Primary penile adenocarcinoma with concurrent hypercalcaemia of malignancy in a dog. (5th November 2014) - Furtado, A. R. R.; Parrinello, L.; Merlo, M.; Di Bella, A.
Abstract : A 13‐year‐old male neutered Siberian husky crossbreed dog was presented with a 3‐week history of haematuria and penile swelling. Clinical examination and computed tomography demonstrated a soft‐tissue mass located at the base of the penis without signs of other primary tumours or metastasis. Clinicopathological findings revealed paraneoplastic hypercalcaemia. Fine‐needle aspiration cytology of the mass suggested an epithelial tumour with several criteria of malignancy present. Following surgical excision of the mass, the hypercalcaemia resolved. Histopathology and immunohistochemistry revealed features consistent with an adenocarcinoma. Despite thorough examination, no perineal or anal sac tumour was found. To the authors' knowledge, this is the first reported case of a penile adenocarcinoma with hypercalcaemia of malignancy.